Women's expectations and experiences of hormone treatment for sexual dysfunction. (December 2014) - Fooladi, E.; Bell, R. J.; Whittaker, A. M.; Davis, S. R.
Abstract Objectives There is a paucity of information regarding women's expectations of medical treatment for female sexual dysfunction (FSD) and their self-appraisal of treatment outcomes. The aims of this study were to explore women's perception and expectations of treatment and their experiences of treatment for FSD using a qualitative approach. Methods First-time attendees to an endocrinologist with the complaint of sexual difficulties were identified and were invited to take part in an in-depth interview on the same day as, but prior to, their medical consultation. Follow-up phone interview took place 3–4 months later. Results Seventeen women, aged 26–70 years, participated in the face-to-face interview. Ten of these participated in the follow-up interview. Four major themes emerged from the women's narrative stories: (1) personal psychological distress associated with FSD, (2) concern about the adverse effect of FSD on the relationship with their sexual partner, (3) a belief in a relationship between FSD and 'hormone deficiency', and (4) an expectation of treatment, which included positive physical and sexual changes. Conclusions Health professionals should be aware of the high degree of psychological distress that can result from FSD and consider available treatment options, which may include hormone therapy.